APPLICATION OF PLAYING METHOD USING LADDER SNAKE GAME MEDIA TO IMPROVE INTELLIGENCE OF KINESTETICS AND LOGICAL MATHEMATICS IN EARLY AGE CHILDREN (Classroom Action Study Group B Year Development PAUD) - Marpini Sri Rejeki; Nina Kurniah (UNIB Press, 2018)
This study aims to improve mathematical kinesthetic and logical intelligence by using the method of playing through the media of modified snakes and ladders in children of group B of the Pembina Negeri PAUD. This type of research is classroom action research. The subjects in this study were 15 children in the B group of the Year Trustees PAUD PAUD consisting of 9 boys and 6 girls. The data collection method used is observation. Data analysis techniques using percent and t-test. The results showed that the application of the playing method using snakes and ladders playing media significantly increased mathematical kinesthetic and logical intelligence. Based on the results of this study, it is recommended to teachers to improve mathematical kinesthetic and logical intelligence as an alternative to being able to use this play method in learning activities.